Muhammadiyah Klaten Regional Leadership Wakaf Management Reviewed from Law Number 41 of 2004 Concerning Wakaf - Balqis Hawwa Fauziyah (Proceeding International Conference Restructuring and Transforming Law, 2023)
A form of worship that aims to get closer to Allah SWT by linking material possessions is waqf. Islam places the practice of waqf as a very beneficial form of worship. This research is empirical juridical research, which means the research was carried out by going directly into the field or obtaining data from the field. The Klaten Muhammadiyah Regional Leadership has a characteristic, namely nazhir which is found in the Klaten Muhammadiyah Regional Leadership in the form of a legal entity, namely a Persyarikatan, because the Muhammadiyah Association cannot carry out its duties directly, the Muhammadiyah Association gives delegation or delegation of authority to someone within the Muhammadiyah Association to become a Nazir. The management of waqf assets in the Klaten Muhammadiyah Regional Leadership is managed professionally in accordance with Islamic regulations and rules, the large amount of waqf assets makes waqf management in the Klaten Muhammadiyah Regional Leadership have a special characteristic, namely Persyarikatan.